Percy Jackson and the Olympians : The Titan's Curse - Book 3 - Riordan, Rick (New York : Disney/Hyperion Books, 2007)
When the goddess Artemis disappears while hunting a rare, ancient monster, a group of her followers joins Percy and his friends in an attempt to find and rescue her before the winter solstice, when her influence is needed to sway the Olympian Council regarding the war with the Titans.
Keywords: Mythology, Greek -- Juvenile fiction; Artemis (Greek deity) -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Monsters -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Mythology, Greek -- Fiction; Artemis (Greek deity) -- Fiction; Animals, Mythical -- Fiction; Monsters -- Fiction; Titans (Mythology) -- Fiction